East Greenland and Faroe-Shetland sediment provenance and Palaeogene sand dispersal systems - Larsen, M.; Knudsen, C.; Frei, D.; Frei, M.; Rasmussen, T.; Whitham, A.G. (Geological Survey of Denmark and Greenland (GEUS), 2006)
The Review of Survey activities presents a selection of 15 papers reflecting the wide spectrum of activities of the Geological Survey of Denmark and Greenland, from the microscopic to the plate tectonic level. Activities in Denmark: The Survey's field of activities in Denmark is illustrated by four papers on petroleum- and groundwater-related topics. Activities in Greenland: The Survey's activities in Greenland and the North Atlantic are covered by ten articles focusing on investigations related to mineral and petroleum exploration and climate research in the Arctic Ocean. Two papers deal with technical aspects of microanalysis by laser ablation techniques and their use in sediment provenance analysis. Activities in other countries: During 2005, the Survey carried out work in more than 20 countries outside Denmark, Greenland and the Faroe Islands. This volume includes an account of a project on developing an environmental sensitivity atlas for the coastal areas of Kenya.